Open Spaces – Dinamic Places: S M L XL - Auböck, Maria; Kárász, János (4D Journal of Landscape Architecture and Garden Art, 2023)
The article offers insights in the design practice of Maria Auböck and János Kárász, landscape architects in Vienna, Austria. The purpose of this text is to mark the occasion of us being awarded honorary professorships at MATE University. The selected methods describe the mission of Landscape Urbanism by presenting a variety of projects, each of them has a history and story of its own. The chosen design methods described include selected inspirations, for instance sketching on site, the choice of plant material and constructive challenges. The main methods applied offer varied aspects of team building, following questions for work cooperation.How can clients be motivated to consider time as a building material that extends beyond their decision-making horizon?How can affordable and attractive landscapes be created based on the insight that within these we are able to provide even added value in economic sense?How can sophisticated empty spaces be introduced in urban sites, and get public acceptance without overstaging them?To summarize the presented project palette the title “Open Spaces – Dynamic Places:  S  M  L  XL” was chosen as the article includes selected works in different scales. The projects include aspects of inner city renovation by example of a baroque monastery’s courtyard and art in public spaces (a memorial of a destroyed synagogue), explaining landscape designs for subsidized housing quarters and the urban greening of Baku- in four steps. The main aspects of the conclusion deals with landscape urbanism, a new field of planning in the challenging time of Climate Change.
Keywords: Landscape Urbanism; Challenges in time of Climate Change; Time is a building material for Landscape Architecture; Poetic spaces offer inspiration